2015
DOI: 10.1104/pp.15.00070
|View full text |Cite
|
Sign up to set email alerts
|

Homeologs of the Nicotiana benthamiana Antiviral ARGONAUTE1 Show Different Susceptibilities to microRNA168-Mediated Control

Abstract: The plant ARGONAUTE1 protein (AGO1) is a central functional component of the posttranscriptional regulation of gene expression and the RNA silencing-based antiviral defense. By genomic and molecular approaches, we here reveal the presence of two homeologs of the AGO1-like gene in Nicotiana benthamiana, NbAGO1-1H and NbAGO1-1L. Both homeologs retain the capacity to transcribe messenger RNAs (mRNAs), which mainly differ in one 18-nucleotide insertion/deletion (indel). The indel does not modify the frame of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 78 publications
6
38
0
Order By: Relevance
“…VIGS-based knockdown screens show severe systemic phenotypic responses when NbAGO1 paralogs are knocked down (Jones et al, 2006). The two NbAGO1 paralogs within N. benthamiana share 97.61% transcript identity and have been termed NbAGO1-H (KR942296) and NbAGO1-L (KR942297) (Jones et al, 2006;Gursinsky et al, 2015). While VIGS assays allow for systemic responses, here we aimed to understand if localized gene editing of a native gene could be observed through NbAGO1 targeting in mature leaf tissue.…”
Section: Trbo-sgrna Targeting Of Native Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…VIGS-based knockdown screens show severe systemic phenotypic responses when NbAGO1 paralogs are knocked down (Jones et al, 2006). The two NbAGO1 paralogs within N. benthamiana share 97.61% transcript identity and have been termed NbAGO1-H (KR942296) and NbAGO1-L (KR942297) (Jones et al, 2006;Gursinsky et al, 2015). While VIGS assays allow for systemic responses, here we aimed to understand if localized gene editing of a native gene could be observed through NbAGO1 targeting in mature leaf tissue.…”
Section: Trbo-sgrna Targeting Of Native Genesmentioning
confidence: 99%
“…The sgRNA targets were identified using the CRISPR design toolset (benchling.com). Gene sequences were used from previously reported and deposited sequences for mgfp5 (Haseloff et al, 1997), NbAGO-L, and NbAGO-H (Gursinsky et al, 2015). The NbAGO-L and NbAGO-H sgRNA (gAGO1) was designed through gene sequence alignment and identification of complementary areas for potential co-targeting (benchling.com).…”
Section: Design Of Sgrnas and Construct Developmentmentioning
confidence: 99%
“…The expression of NbAGO10b or the other AGO s was not greatly affected in NbAGO10a ‐silenced plants (Figs b, S4a). It was reported previously that the accumulation levels of two homeologs of NbAGO1a , NbAGO1‐1H and ‐1L , were differently affected by the regulation of miR168 or tombusvirus infections (Gursinsky et al ., ). However, the accumulation levels of both NbAGO1‐1H and ‐1L were not significantly affected in NbAGO10 ‐silenced N. benthamiana (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…NbAGO2 also has been implicated in resistance to suppressor-defective PVX (Fatyol et al, 2016). Recently, it has been shown that silencing of two NbAGO1 homeologs, NbAGO1-1H and NbAGO1-1L, causes different symptoms in tombusvirus-infected N. benthamian (Gursinsky et al, 2015). The major difference between these two homeologs is an insertion/deletion (indel) of 18 nucleotides (nt) located 8 nt upstream of the target site of miR168 that guides post-transcriptional gene silencing (PTGS) of NbAGO1 mRNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation